Ehlers-Danlos Syndrome Type IV: A Case Report. (April 2016) - Soo-Hoo, Sarah; Porten, Brandon R.; Engstrom, Bjorn I.; Skeik, Nedaa
Ehlers-Danlos syndrome (EDS) encompasses a group of rare genetic connective tissue disorders. The vascular type (type IV) poses the most serious risk to patients. Diagnosis is usually difficult, especially if patients lack a family history. Life-threatening vascular emergency such as dissection or rupture can be the first presenting symptom. Management of the disease can pose a clinical challenge due to the emergency of presentation, tissue friability, and lack of clear management recommendations. We report a unique case of a 40-year-old man who presented with a ruptured celiac artery and a strong family history of EDS. This case highlights the difficulties and complications associated with treating this uncommon and serious disease.